2019
DOI: 10.1097/jnr.0000000000000291
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Workplace Violence, and Burnout in Nurses Working in King Abdullah Medical City During Al-Hajj Season

Abstract: Background: The Hajj pilgrimage to Mecca, one of the largest mass gatherings in the world, is associated with various challenges for nurses. One of these challenges is increased levels of workplace violence. Therefore, handling and mitigating workplace violence against nurses during Hajj, when nurses face a higher risk of violence and most experience stress and burnout, is of particular importance. Purpose: The aims of this study were to identify the types and sources o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 25 publications
3
50
1
3
Order By: Relevance
“…Mobbing against nurses is a common phenomenon in Healthcare facilities that affects not only nurses, but also patients, the quality of the services provided by health care institutions, even patient mortality. [1][2][3][4] The main effect of mobbing on nurses is that it makes them try to change their workplace in the institution, try to find another institution to work for, or even try to change their profession if an opportunity arises. 5 For a problem to be solved it has to be firstly reported.…”
Section: Mobbing Against Nurses: a Serious Problem That Has To Be Solvedmentioning
confidence: 99%
“…Mobbing against nurses is a common phenomenon in Healthcare facilities that affects not only nurses, but also patients, the quality of the services provided by health care institutions, even patient mortality. [1][2][3][4] The main effect of mobbing on nurses is that it makes them try to change their workplace in the institution, try to find another institution to work for, or even try to change their profession if an opportunity arises. 5 For a problem to be solved it has to be firstly reported.…”
Section: Mobbing Against Nurses: a Serious Problem That Has To Be Solvedmentioning
confidence: 99%
“…The Hajj is a five-day holy pilgrimage and represents one of the largest annual mass gatherings in the world. Nurses represent key members of the healthcare team responsible for providing services that care for Hajj pilgrims who are injured or ill (Alzahrani & Kyratsis 2017;Kemp 2016;Rayan et al 2019;WHO 2015). Aldossari et al's (2019) review concluded that during successive Hajj seasons, new public health challenges emerge, and the authors urge Saudi's Ministry of Health (MOH) to continue to improve public health management during Hajj.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence shows how nurses and other staff in the hospitals, medical centres and directorates treating visitors to Mecca and Medina during Hajj face challenges. For instance, the increased risk of emergency situations with some people requiring specialized medical care, coupled with a need to treat higher volumes of people quickly, puts great pressure on healthcare professionals and the services they provide (Rayan et al 2019). Previous research suggests nurses can experience stress and burnout due to their increased workload and the unique problems and professional challenges they encounter during Hajj (Alzahrani & Kyratsis 2017;Rayan et al 2019;Sulaiman et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations